AIDS Updates Recent Advances and New Perspectives - Ikwaras Okware, Samuel (IntechOpen, 2021)
Significant progress in HIV prevention and control has been achieved worldwide. This book reviews emerging challenges and new opportunities for prevention. Chapters cover such topics as challenges in the media within the context of advancing technologies and societal perceptions, barriers to antiretroviral treatment and suggestions for improvement, opportunities in nanotechnology-based drug delivery systems, the central role of sexual and reproductive health in consolidating a human rights-based program, and much more. Client-focused models for integrating employment as a social determinant in the HIV/AIDS programs are discussed and recommended.